Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD GMIM Tokin - Deddy F. Kumolontang (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this research is to find out how to apply problem-based learning methods to improve student learning outcomes in social science learning. The research was conducted at SD GMIM Tokin, South Minahasa, with the research subjects being fourth grade students. This research is an action research using the Kemmis and McTaggart model, which was conducted for two cycles. Each cycle consists of stages of planning, implementing actions, observing, and reflecting on actions. Action observation data in the process of learning activities during the action is carried out using problem-based learning methods. The results of the percentage of classical learning completeness in the first cycle were only 58.67%. It was found that the students' learning mastery level was 7 students who were able to complete the learning process. While the percentage of classical learning completeness increased significantly in the second cycle which was only 91.67%. It was found that the level of completeness of student learning increased with a number of 15 students being able to complete the learning process. Based on the implementation of research using a problem-based learning model, it can be said that the problem-based learning model can improve the learning outcomes of fourth students at the GMIM Tokin Minahasa Selatan elementary school.